اضطرابات الوظيفة الجنسية عند الذكور الفصاميين في سورية - ربيع غياث (Latakia University Journal -Medical Sciences Series, 2017)
تمت دراسة /75/ مريض فصام ذكر متزوج بأعمار تفاوتت بين /16 – 60/ سنة ممن راجعوا العيادة النفسية في مشفى الأسد والعيادة الخاصة خلال /12 شهراً ( عام كامل ) 2012/ الطرق المستخدمة // DSM –IV – TR التصنيف الأمريكي للأمراض النفسية الطبقة الرابعة المعدلة والمدرج التشخيصي الجنسي " اريزونا " كما عوملت النتائج احصائياً وقبلت /P≤ 0.05/واعتبرت النتائج موثوقة عندها النتائج أظهرت نسبة /82%/ من المرضى الفصاميين الذكور كان لديهم اضطراب في الوظيفة الجنسية متوسط العمر كان (47)عاماً .كان هناك علاقة مهمة بين العمر واضطرابات الوظيفة الجنسية وكذلك الحالة الوظيفية .من يعمل أقل تأثراً بوظيفته الجنسية وكذلك بين مستوى التعليم ونسبة الاضطرابات حيث شكل الأميَون أكثرية المرضى/ 58.73% / من المضطربين جنسياً عند ذكر نسب الاضطرابات الجنسية : الرغبة/20%/ الانتصاب/53.33%/ الأورجازم/9.33%/ التوصيات : الاضطرابات الوظيفية الجنسية في أمراض الفصاميين الذكور في مجتمعنا نسبة كبيرة مما يستدعي أخذ ذلك بعين الاعتبار حين تقييم المرضى الفصاميين ووضع الخطط المناسبة لذلك . To assess and find out the impact of schizophrenia on sexuality of the patient using /DSM- IV – TR/ andasexscale questionnaires for/ 75/ male , were studied in clinic . the study extended for /24 /month one year/ 2012/. so were used statistical analysis ./ P≤O.5/ used as cut off significance. Eighty two percent of schizophrenic male in this study got sexual dysfunction , ther ages (16 – 60) with mean/ 47/ year , there was significant association between age and sexual function- although between degree of education- and sexual function Were percent /58,73%/, result , showed that significant association between getting better education al level and better sexual function results showed that patients have employed patients got worse effect on sexual function so more duration of treatme caused worse effect on sexuality .when patients classified by type of sexual disorder :disere/ 20% /, arousal/ 53.33%/, orgasm /9.33%/ Sexual dysfunction in schizophrenics is common in mal in Syria our communiny and evaluating be routinely in quired from patients with schizophrenia receving antipsychotics medication